2019
DOI: 10.3390/jcm8091382
|View full text |Cite
|
Sign up to set email alerts
|

Chronic Use of Proton-Pump Inhibitors and Iron Status in Renal Transplant Recipients

Abstract: Proton-pump inhibitor (PPI) use may influence intestinal iron absorption. Low iron status and iron deficiency (ID) are frequent medical problems in renal transplant recipients (RTR). We hypothesized that chronic PPI use is associated with lower iron status and ID in RTR. Serum iron, ferritin, transferrin saturation (TSAT), and hemoglobin were measured in 646 stable outpatient RTR with a functioning allograft for ≥ 1 year from the “TransplantLines Food and Nutrition Biobank and Cohort Study” (NCT02811835). Medi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
27
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(28 citation statements)
references
References 47 publications
0
27
0
1
Order By: Relevance
“…It has been widely documented that PPIs may affect absorption of micronutrients, leading to deficiencies of important electrolytes, including iron and magnesium PLOS MEDICINE [11,14,15]. Indeed, we previously found that PPI use was associated with iron deficiency and hypomagnesemia in KTRs [37,39]. Iron deficiency can in turn lead to iron deficiency anemia, which has been linked to a higher graft failure risk and mortality risk in KTRs [40][41][42].…”
Section: Plos Medicinementioning
confidence: 88%
See 1 more Smart Citation
“…It has been widely documented that PPIs may affect absorption of micronutrients, leading to deficiencies of important electrolytes, including iron and magnesium PLOS MEDICINE [11,14,15]. Indeed, we previously found that PPI use was associated with iron deficiency and hypomagnesemia in KTRs [37,39]. Iron deficiency can in turn lead to iron deficiency anemia, which has been linked to a higher graft failure risk and mortality risk in KTRs [40][41][42].…”
Section: Plos Medicinementioning
confidence: 88%
“…To explore a potential dose-response relationship, we performed additional Cox regression analyses in which KTRs were divided into 3 groups based on daily PPI dose defined in omeprazole equivalents: no PPI, low PPI dose (�20 mg omeprazole equivalents/day), and high PPI dose (>20 mg omeprazole equivalents/day) as described previously [37]. Tests of linear trend were conducted by assigning the median of daily PPI dose equivalents in subgroups treated as a continuous variable.…”
Section: Plos Medicinementioning
confidence: 99%
“…PPI type and daily dosage were obtained from electronic patient records and are demonstrated in Table S1. KTR using any PPI on a daily basis during a period of at least 3 months prior to the study visit were defined as chronic PPI users as described previously [24]. To investigate a potential dose-response relationship, KTR were divided into three groups based on daily PPI dose defined in omeprazole equivalents: no PPI, low PPI dose (≤20 mg omeprazole equivalents/day (Eq/day)) and high PPI dose (>20 mg omeprazole Eq/day) [24,25].…”
Section: Exposure Definitionmentioning
confidence: 99%
“…Effect modification by loop diuretics, thiazide diuretics, tacrolimus and diabetes was tested by inclusion of interaction terms. To investigate a potential dose-response relationship we performed additional analyses in which KTR were divided into three groups based on daily PPI dose defined in omeprazole equivalents: No PPI, low PPI dose (≤20 mg omeprazole Eq/day) and high PPI dose (>20 mg omeprazole Eq/day) [24,25]. Tests of linear trend were conducted by assigning the median of daily PPI dose equivalents in subgroups treated as a continuous variable.…”
Section: Statistical Analysesmentioning
confidence: 99%
“…16,17 Other transplant studies have demonstrated associations between PPI use and hypomagnesemia, Clostridium difficile infections, iron deficiency anemia, and increased fracture risk. [18][19][20][21][22][23][24] However, these studies did not compare PPIs to H2RAs [18][19][20][21][22] and included relatively small cohorts. 23,24 Most studies comparing the impact of PPI or H2RA use on renal function posttransplant report outcomes up to a year posttransplant.…”
mentioning
confidence: 99%